Fiscal policy under financial stress: a threshold VAR approach - Jóia, Filipa Gomes da Silva (2015)
The purpose of the project is to measure the impact of fiscal policy on the Portuguese GDP and how it may vary according to the state of the financial market. A Threshold VAR model is presented in which the two regimes are found using a financial stress index that divides the economy into a situation of financial stress and financial stability.